The study on the public perception of LRT system to reduce the traffic congestion in Kuching / Marcion John and Jean Cloude Chanat - John, Marcion; Chanat, Jean Cloude (2017)
The population of Kuching is increasing throughout the last decade and that means there will be a lot of traffic vehicle on the road. Earlier this year, within the month of March 2017, Sarawak’s Chief Minister Datuk Amar Abang Johari Tun Openg announce the planning to build and to have a Light Rail Transit (LRT) system that connects Kuching which is the state’s capital with Samarahan and Serian District. This study in general is to know what is the public perception on having a Light Rail Transit system in Kuching city through the objectives that we would want to achieve later. Perhaps, in the future, the citizen of Kuching may enjoy the benefits once the Light Rail Transit system is established.